(untitled) - The World Bank (WB) (Ha Noi, 2009)
This Vietnam development report focuses on devolution and accountability, two aspects of modern institutions that are the essense of Vietnam's experience in the past two decades
Keywords: Communism,Chủ nghĩa Cộng sản; Vietnam,Việt Nam